Codition of Coral Reef at Teluk Pandan Sub-District East Kutai District - Muhammad Syahrir R; Achmad Jayadi; Adnan Adnan; Muhammad Yasser MF; Tedy Hanjoko (Chemical Engineering Diponegoro University, 2015)
Coral reef of TelukPandan Sub-district East Kutai District still low in both monitoring and management, thus also poorly in coral reef database. This research purpose was to obtain the data of coral reef condition and distribution description in this sub-district. Research was held on October 2013 at six observation stations using lifeform line intercept transect survey method. The coral condition estimation was based on live coral cover (LC) and hard coral mortality index (HCM). Coral reef distribution and wide were estimated by satellite image Landsat 7 ETM+ processing and direct field tracking using GPS. There estimated ± 618.63 ha of coral reef area consist of fringing and patch reef formation type. Live coral cover vary 2.1-67.8% or categorized “poor” to “good” reef condition and in average LC = 38.1% (“fair/moderate” condition). Hard coral morality (HCM) index ranged 0.14 – 0.8 and in average 0.31.